Optimalisasi Prosedur Pemeliharaan Ruang Muat dan Perlindungan Muatan Kontainer pada MV Meratus Kariangau - Juan Calvin Tominu; Mudiyanto Mudiyanto; Teguh Wiyono (Port Management and Maritime Administration Journal, 2026)
The safety and quality of container cargo during sea transportation are highly influenced by the condition of cargo holds and the effectiveness of maintenance procedures. This study aims to analyze the implementation of maintenance and protection procedures for container cargo in the in-hole area of MV Meratus Kariangau, particularly related to cargo hold maintenance, Bilge system performance, and cargo space supervision. This study employed a qualitative descriptive approach, while data were collected through observation, semi-structured interviews, and documentation. The results reveal that cargo hold maintenance has been routinely performed; however, their implementation has not yet been fully optimized due to operational time constraints, the presence of residual moisture and standing water in certain areas, and the suboptimal performance of the Bilge alarm system. In addition, cargo space supervision is still conducted based on operational conditions and lacks a structured inspection schedule. These findings imply the need to improve preventive maintenance systems, conduct regular inspections and testing of Bilge and Bilge alarm systems, and establish a more systematic cargo hold supervision procedure to minimize the risk of container cargo damage during voyages.